In vivo Visualization of Pig Vagus Nerve “Vagotopy” Using Ultrasound - Settell, Megan L.; Skubal, Aaron C.; Chen, Rex C. H.; Kasole, Maïsha; Knudsen, Bruce E.; Nicolai, Evan N.; Huang, Chengwu; Zhou, Chenyun; Trevathan, James K.; Upadhye, Aniruddha; Kolluru, Chaitanya; Shoffstall, Andrew J.; et al. (Frontiers in Neuroscience, 2021)
Please see the abstract in the uploaded file. The reviewed manuscript has an abstract 100 words over the specified limit and was approved by reviewers in this version in revisions, therefore I was unsure if I should alter the abstract post-approval. Please feel free to reach out with any questions.